Synthesis and antimycobacterial evaluation of pyrazinamide derivatives with benzylamino substitution - Zitko, Jan; Paterová, Pavla; Kubíček, Vladimír; Mandíková, Jana; Trejtnar, František; Kuneš, Jiří; Doležal, Martin (Bioorganic & medicinal chemistry letters, 2013)
A series of 19 new compounds related to pyrazinamide were synthesized, characterized with analytical data and screened for in vitro whole cell antimycobacterial activity against Mycobacterium tuberculosis H37Rv, Mycobacterium kansasii and two types of Mycobacterium avium. The series consisted of 3-(benzylamino)-5-cyanopyrazine-2-carboxamides and 3-(benzylamino)pyrazine-2,5-dicarbonitriles with various substituents on the phenyl ring. RP-HPLC method was used to determine the lipophilicity of the prepared compounds. Nine compounds exerted similar or better activity against Mycobacterium tuberculosis compared to pyrazinamide (MIC=6.25-12.5 μg/mL). 3-(Benzylamino)pyrazine-2,5-dicarbonitrile inhibited all of the tested mycobacterial strains with MIC within the range 12.5-25 μg/mL. Although not the most active, 4-NH(2) substituted compounds possessed the lowest in vitro cytotoxicity (hepatotoxicity), leading to selectivity index SI=5.5 and SI >21.
Keywords: Benzylamines; Molecular Structure; Mycobacterium; pyrazinamid; benzylaminy; lidé; molekulární struktura; Antitubercular Agents; Cells, Cultured; antituberkulotika; Microbial Sensitivity Tests; mikrobiální testy citlivosti; inhibiční koncentrace 50; Inhibitory Concentration 50; Pyrazinamide; kultivované buňky; Humans